2023
DOI: 10.1161/jaha.123.029689
|View full text |Cite
|
Sign up to set email alerts
|

Causal Association Between Anemia and Cardiovascular Disease: A 2‐Sample Bidirectional Mendelian Randomization Study

Abstract: Background Although previous observational studies have shown an association between anemia and cardiovascular disease (CVD), the underlying causal relationship between anemia and CVD remains uncertain. Methods and Results We conducted a 2‐sample bidirectional Mendelian randomization (MR) study to assess the causal association between anemia and CVD. We extracted summary statistics data for anemia, heart failure (HF), coronary artery dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…These results align with earlier studies by Lanser et al, which also reported an association between anemia and the progressive severity of CAD (Lanser et al, 2021). Findings in other studies also found a link between anemia and heart disease such as heart failure (Gan et al, 2023)The complex pathophysiological mechanisms underlying anemia in cardiovascular disease and CAD involve a multitude of factors. Anemia initiates immediate hemodynamic shifts, influencing blood viscosity, arterial dilation, vascular resistance, and stroke volume (Metivier et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…These results align with earlier studies by Lanser et al, which also reported an association between anemia and the progressive severity of CAD (Lanser et al, 2021). Findings in other studies also found a link between anemia and heart disease such as heart failure (Gan et al, 2023)The complex pathophysiological mechanisms underlying anemia in cardiovascular disease and CAD involve a multitude of factors. Anemia initiates immediate hemodynamic shifts, influencing blood viscosity, arterial dilation, vascular resistance, and stroke volume (Metivier et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, linkage disequilibrium filtering ( r 2 =0.001, window size=10 000 kb) was performed to select independent SNPs. 13 , 14 As F ‐statistics represent the magnitude of the genetic instruments, we calculated SNPs for all included studies to ensure that the F ‐statistics were >10 to minimize weak instrument bias. The F ‐statistics were used for F = R 2 ( N −2)/(1− R 2 ), where R 2 represents the proportion of the variability of the exposure explained by IVs, and N represents the sample size of the GWAS for BMR.…”
Section: Methodsmentioning
confidence: 99%
“…Sensitivity analysis was performed by removing each SNP from the original MR analysis. In the leave-one-out sensitivity analysis we used forest plot to express the results, which can detect whether the results were disproportionately affected by any single SNP (Gan et al, 2023). Finally, heterogeneity evaluation was performed by the inverse variance weighting (IVW) model, and the signi cant threshold was set as P < 0.05 (Riaz et al, 2018).…”
Section: Sensitivity Analysismentioning
confidence: 99%